'The seas are rising and so are we!' – a conversation between two women in Extinction Rebellion. Issue 3 (1st September 2020) - Smyth, Ines; Walters, Lucy
ABSTRACT: Extinction Rebellion (XR) is an international, non-violent movement against the climate and ecological crises that threaten our planet. This article is based on reflections and joint discussions on what it is to be women 'rebels' at the grassroots of this movement, utilising the feminist practice of 'active listening' to counter women's experiences of being silenced or ignored. Our point of departure in writing this article was the idea that even in the most progressive movements, structures and dynamics tend to mirror unequal gender relations typical of wider society. Despite our differences in age, background, and experiences as activists, our conversations led us to agree that the values and culture of XR allow us, as women and as feminists, to be comfortable in our skin; to be heard; to be bold in challenging stereotypes, explore and express new and sometimes painful emotions, and push social and personal boundaries. We felt that XR also experiences some challenges: a reluctance to embrace more explicitly 'climate justice', an insufficient concern for gender equality as part of its focus on this, and echoes of essentialist links between women and nature.